10.4: Improvement of Stability on a‐IGZO LCD. Issue 1 (1st July 2013) - Wu, Chun Wei; Yoo, Seong Yeol; Ning, Ce; Yang, Wei; Shang, Guang Liang; Wang, Ke; Liu, Chien Hung; Liu, Xiang; Yuan, Guang Cai; Chen, Jian; Xu, Yubo; Lee, Woobong; et al.
Abstract: We have developed 10‐inch 300PPI and 65‐inch ultra high‐definition FFS LCD using amorphous In‐Ga‐Zn‐O(IGZO) TFT. After improvement of TFT's process and structure, the TFT performance is good enough for TFT‐LCD. In this report, we discuss our IGZO TFT process, uniformity and reliability.